J Neurol Res Rev Rep 2020
DOI: 10.47363/jnrrr/2020(2)117
|View full text |Cite
|
Sign up to set email alerts
|

Better Use of Scales as Measuring Instruments in Mental Disorders

Abstract: Objective: Linearity implies high correlation but the converse is not true. For meaningful application of correlation and other descriptive and inferential analysis, checking of linearity, and assumptions of correlation including normality are needed The paper describes method of converting ordinal scores from Likert/ Rating scale to continuous, monotonic, equi-distant scores with fixed zero point and following normal distribution. Method: The method involves selection of weights for different response categ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Proposed method [28] proposed method of converting ordinal scores of i-th item to continuous scores satisfying equidistant property (-scores) in ratio scale and further transforming -scores linearly to proposed scores(-scores) in ratio scale and further transforming -scores linearly to proposed scores (-scores) where…”
Section: Xmentioning
confidence: 99%
“…Proposed method [28] proposed method of converting ordinal scores of i-th item to continuous scores satisfying equidistant property (-scores) in ratio scale and further transforming -scores linearly to proposed scores(-scores) in ratio scale and further transforming -scores linearly to proposed scores (-scores) where…”
Section: Xmentioning
confidence: 99%
“…In addition, desirable properties of the weighted sum need to be specified beforehand. Chakrabartty (2020) where 𝑅 is the correlation matrix and 𝑖 ≠ 𝑗. Greco et al (2019) observed that no weighting system is above criticism.…”
Section: Introductionmentioning
confidence: 99%